STUDY ON ENGLISH LANGUAGE EVALUATION STANDARDS - Tumurbat, Oyun-Erdene; Sergelen, Namuun (UC Journal: ELT, Linguistics and Literature Journal, 2022)
There are several evaluation standards to assess English levels. Through this article, we consider the Common European Framework of Reference (CEFR) as an important tool. We aimed to reveal the evaluation standards used in universities and English language training courses in our country and to clarify how the standard tolerates internationally accepted English language evaluation standards. Within the scope of this goal, 27 teachers who teach English in universities and colleges in Mongolia, 22 teachers of English language training centers (general informants), and 656 students who study English in 21 universities and colleges in Mongolia (casual informants) were randomly selected and a survey with 3 groups of 24 questions was conducted over 2 months using Google Form, and the collected results were processed and compared using SPSS program.96.3% of the teachers of universities and colleges evaluate the English course on a 100-point scale. 55.5% of them agreed that the future use of CEFR assessment standards would provide a more objective assessment of students' language levels. According to the responses of training center teachers, 68.2% of the participating training center teachers evaluate the student's language level according to the CEFR standard, which shows that they use an internationally recognized evaluation method. In this regard, 42.7% of the 656 students who participated in the study agreed that the CEFR assessment standard, rather than the 100-point scale, could fully reflect their language level internationally in the future, which was in line with the researchers' hypothesis.